2007
DOI: 10.1007/978-3-540-72588-6_121
|View full text |Cite
|
Sign up to set email alerts
|

Quantization Error and Accuracy-Performance Tradeoffs for Embedded Data Mining Workloads

Abstract: Abstract. Data mining is the process of automatically finding implicit, previously unknown and potentially useful information from large volumes of data. Embedded systems are increasingly used for sophisticated data mining algorithms to make intelligent decisions while storing and analyzing data. Since data mining applications are designed and implemented considering the resources available on a conventional computing platform, their performance degrades when executed on an embedded system. In this paper, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Trading accuracy of computation for other benefits is a wellknown technique. It has been shown that one can trade off accuracy for performance [17,32,40,43,44], energy consumption [13,14,17,21,34,43,47] and fault tolerance [14,43,47]. The Dynamic Knobs system presented in this paper, along with loop perforation [27,39] and task skipping [43,44], is unique in that it enables applications to adaptively trade accuracy for performance and does so without requiring a developer to change the application source code.…”
Section: Related Workmentioning
confidence: 99%
“…Trading accuracy of computation for other benefits is a wellknown technique. It has been shown that one can trade off accuracy for performance [17,32,40,43,44], energy consumption [13,14,17,21,34,43,47] and fault tolerance [14,43,47]. The Dynamic Knobs system presented in this paper, along with loop perforation [27,39] and task skipping [43,44], is unique in that it enables applications to adaptively trade accuracy for performance and does so without requiring a developer to change the application source code.…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that one can trade off accuracy for performance [16,32,40,43,44], energy consumption [12,13,16,20,34,43,47] and fault tolerance [13,43,47]. The Dynamic Knobs system presented in this paper, along with loop perforation [26,39] and task skipping [43,44], is unique in that it enables applications to adaptively trade accuracy for performance and does so without requiring a developer to change the application source code.…”
Section: Related Workmentioning
confidence: 99%
“…Algorithms implemented using fixed-point arithmetic [11] trade precision for energy-and-computational efficiency, replacing expensive floating-point operations with a sequence of faster integer operations. Compute-intensive parts of kernels described in Table I depend heavily on of resources on accelators like FPGAs, making them prime candidates for fixed-point optimization.…”
Section: Approximate Analyticsmentioning
confidence: 99%